2000
DOI: 10.1096/fj.00-0134com
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1‐phosphate released from platelets during clotting accounts for the potent endothelial cell chemotactic activity of blood serum and provides a novel link between hemostasis and angiogenesis

Abstract: Recent studies have identified factors responsible for angiogenesis within developing tumors, but mediators of vessel formation at sites of trauma, injury, and wound healing are not clearly established. Here we show that sphingosine 1-phosphate (S1P) released by platelets during blood clotting is a potent, specific, and selective endothelial cell chemoattractant that accounts for most of the strong endothelial cell chemotactic activity of blood serum, an activity that is markedly diminished in plasma. Preincub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
221
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(227 citation statements)
references
References 29 publications
5
221
0
1
Order By: Relevance
“…The lower S1P levels in plasma relative to serum (Fig. 2D, inset) are consistent with S1P release by platelets during blood clotting (42,43).…”
Section: Fty720 Is Phosphorylated and Causes Lymphopenia In Sphk1 Nullsupporting
confidence: 70%
“…The lower S1P levels in plasma relative to serum (Fig. 2D, inset) are consistent with S1P release by platelets during blood clotting (42,43).…”
Section: Fty720 Is Phosphorylated and Causes Lymphopenia In Sphk1 Nullsupporting
confidence: 70%
“…The influence of PMV on chemotaxis, for example, may be attributed to the presence of S1P or AA. 13,20,52 Unsaturated acids, however, have been found to induce apoptosis and inhibit proliferation in several other experimental systems. 13,52 Our previous studies have demonstrated that the biologic activity of PMV is associated with high-molecular-weight proteins and is only partly affected by protein digest and/or heat inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…13,20,52 Unsaturated acids, however, have been found to induce apoptosis and inhibit proliferation in several other experimental systems. 13,52 Our previous studies have demonstrated that the biologic activity of PMV is associated with high-molecular-weight proteins and is only partly affected by protein digest and/or heat inactivation. 12 We suggested that it could be related partly to high-molecular-weight, relatively temperature-stable proteins and partly to bioactive lipids conjugated with high-molecular-weight proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems likely that S1P, which is known to be abundantly stored in platelets and released on their activation, 17 may contribute to plateletinduced angiogenesis in wound repair, because it was demonstrated that S1P is the major EC chemoattractant released into serum by platelets during blood clotting. 18 Therefore, it is suggested that the angiogenic activity of S1P may account for the important role of platelet interaction with ECs in angiogenesis at sites of injury. Interestingly, previous studies have demonstrated the crucial role of NO in wound healing, as wound healing is accelerated by systemic administration of L-arginine, a substrate of NOS, but delayed by NOS inhibitors.…”
Section: Discussionmentioning
confidence: 99%